The Legal Nature of Cryptocurrencies: Analyzing Potential Regulatory Approaches in the United Arab Emirates and the Kingdom Saudi Arabia - Habadi, Ghaida; Alsamara, Tareck (Journal of Ecohumanism, 2025)
The classification and regulation of cryptocurrencies have been the subject of substantial legal and academic debates, particularly in the rapidly evolving contexts of the United Arab Emirates and Saudi Arabia. This article investigates the legal nature of cryptocurrencies by analyzing their fundamental attributes, classification as commodities or currencies, and the extent to which they are supported by tangible assets. This article examines the intrinsic properties of a variety of cryptocurrencies, and the extent to which they are supported by tangible assets. In addition, the article explores the jurisprudential debate within the United Arab Emirates and Saudi Arabia, emphasizing differences in viewpoints regarding the legal and economic ramifications of cryptocurrencies. The aim of this article is to provide a thorough understanding of the legal nature of cryptocurrencies and how their characteristics influence the regulation of these currencies in Saudi Arabia and the United Arab Emirates.